The Influence Of Financial Innovation And Financial Ratio On The Financial Performance Of The Banking Sector - Diana Purnamasari (Jurnal Perbankan Syariah, 2024)
Financial performance involves analyzing how well a company adheres to financial regulations and standards. This study investigates the impact of financial innovation and financial ratios on the performance of banking companies from 2009 to 2018. The research employs a descriptive approach with quantitative methods, utilizing secondary data. Purposive sampling is the chosen sampling method. Data analysis is conducted using panel regression analysis techniques, which include the Chow test, Hausman test, Lagrange multiplier test, classical assumption test, and partial regression test. The findings indicate that the NPL ratio has a significant negative effect on ROA, the LDR ratio has a significant positive effect on ROA, while the financial innovation variable and CAR had no effect on ROA